Purchase order for the engagement of the designer for the design of railing and henna ceiling for BRACU new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Saidul Haque for the engagement of the designer for the design of railing and henna ceiling for BRACU new campus project.